2002
DOI: 10.1063/1.1471931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pd or Pt addition to Ti/Al ohmic contact materials for n-type AlGaN

Abstract: Effects of Pd or Pt addition to Ti/Al ohmic contact materials used for n-type Al0.2Ga0.8N grown on the GaN substrates were studied where Si with 2×1018 cm−3 were doped in the AlGaN layers. The contact metals were prepared by depositing either by the electron-beam or thermal evaporation technique, and then annealed at high temperatures for 30 s in N2 atmosphere. It was found that the addition of a small amount of Pd or Pt to the Ti/Al ohmic contact materials reduced the contact resistivities of the Ti/Al contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…The Mo reacts with the Ga of the AlGaN layer and causes the generation of Ga vacancies at the AlGaN surface. It has been reported that Ga outdiffusion enhanced by reacting Pd or Pt reduces contact resistance [5]. However, Pd and Pt have a high work function, so diffusion to the semiconductor with hightemperature annealing results in a Schottky contact.…”
mentioning
confidence: 99%
“…The Mo reacts with the Ga of the AlGaN layer and causes the generation of Ga vacancies at the AlGaN surface. It has been reported that Ga outdiffusion enhanced by reacting Pd or Pt reduces contact resistance [5]. However, Pd and Pt have a high work function, so diffusion to the semiconductor with hightemperature annealing results in a Schottky contact.…”
mentioning
confidence: 99%
“…1. It was shown that the as-deposited sample exhibited a non-linear I-V characteristic due to the large work function of the p-GaN (>7.5 eV) [27,28]. However, the linearity of the I-V curves becomes improved with increasing annealing temperature.…”
Section: Resultsmentioning
confidence: 96%
“…More recently, promising approaches using Ni-based alloys such as Ni-La, Ni-Zn, Ni-Mg, and Ni-Cu produced very low specific contact resistivity in 10 −5 ∼10 −6 cm 2 range, depending on metal schemes [15][16][17][18]. From those approaches, Ni/Au is although being used as p-contact electrode for conventional InGaN/GaN LEDs, various Pt-and Pd-based ohmic contact such as Pt/Ni/Au, Pt/Ru, Pt, Pt/Au, Ti/Pt/Au, Pd/Au, Pd/Ni, Pd/Pt/Au, Pt/Pd/Au, and Pd/Ag/Au/Ti/Au also have been investigated significantly due to the fact that those metals have large work functions and easily react with gallium during an annealing process [7,13,[19][20][21][22][23][24][25][26][27][28][29]. The specific contact resistivities of both the Pt-and Pd-based ohmic contacts are typically in the range of low 10 −3 ∼10 −5 cm 2 .…”
mentioning
confidence: 99%
“…3,6,8,90 Ohmic contact to n-type Al x Ga 1-x N.-For n-type Al x Ga 1-x N, ohmic contacts can be easily formed by using Ti/Al-based or V/Albased metal schemes. [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] The Ti/Al-based metal schemes are generally used as contacts to n-Al x Ga 1-x N, producing contact resistivities of 10 −4 −10 −6 cm 2 after annealing at high temperatures. [91][92][93][94][95][96] The ohmic contact formation was explained by the formation of AlN and TiN phases, generating donor-like nitrogen vacancies (V N ) and hence increasing donor concentrations near the surface region.…”
Section: Ohmic Contacts For Deep Uv Ledsmentioning
confidence: 99%
“…[91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] The Ti/Al-based metal schemes are generally used as contacts to n-Al x Ga 1-x N, producing contact resistivities of 10 −4 −10 −6 cm 2 after annealing at high temperatures. [91][92][93][94][95][96] The ohmic contact formation was explained by the formation of AlN and TiN phases, generating donor-like nitrogen vacancies (V N ) and hence increasing donor concentrations near the surface region. 92,98,104 However, Ti/Al-based contacts had a tendency to form Schottky behavior as the Al mole fraction increases, 104,105 while V/Al-based schemes provided lower contact resistance due to the formation of vanadium nitride (VN).…”
Section: Ohmic Contacts For Deep Uv Ledsmentioning
confidence: 99%